Developing the process skills in science among fast learners in the intermediate grades - Musa, Diomeda S. 1944-; Baldo, Trinidad C. (1973)
Following the principle that modern science teaching should stress the processes of science rather than the accumulation of facts, the study discussed the process skills to be developed among the fast learners in the intermediate grades and suggested some promising methods, techniques and activities to build, develop, and strengthen the process skills among these youth. Among the methods, techniques and activities selected are: invitation to inquiry, field trips, inquiry session, laboratory experiences, invitation to discovery, counter-intuitive science events, pictorial science riddles, simulation or use of games in the classroom, and discovery questioning techniques. It is believed that the selected methods, techniques and activities will lend themselves to self-direction and will have special appeal to the fast learners in the intermediate grades.
Vita.
Thesis (Master of Arts in Teaching - Special Education : Mentally Gifted)--University of the Philippines, Diliman.
Keywords: Science -- Study and teaching (Elementary) -- Philippines; Gifted children -- Education (Elementary) -- Philippines